Rectifier condition monitoring for brushless synchronous generators - Wong, Wee Kian (2018)
Brushless Synchronous Generators (BLSG) are widely used in the industry, being one of the most commonly used machinery, they are likely prompt to failures and faults. BLSG failures can be caused by both mechanical and electrical failures, however one of the most critical failures in this machine is associated with the rotating rectifier used in the rotor. The 3-phase rotating rectifier comprises of six individual diode, the function of the rectifier is to convert alternative current (AC) power to direct current (DC) power. For every diode, they have a typical voltage-current (VI) characterise curve and as the diode degenerate, its VI characteristic curve changes as well. As such, accelerated aging were conducted to examine the changes in diodes VI characteristic curves and how does it affect its individual performances as a diode and overall performances as a rectifier. // The results of this research shows that, as the diode degenerate, its resistance increases, voltage across the diode increases and the DC output voltage and current increases. This converge results can actually be seen throughout the whole research, under all testing conductions.